Ketalization of ketones to 1,3-dioxolanes and concurring self-aldolization catalyzed by an amorphous, hydrophilic SiO2-SO3H catalyst under microwave irradiation - Barbosa, Sandro L.; Ottone, Myrlene; De Almeida, Mainara T.; Lage, Guilherme L.C.; Almeida, Melina A.R.; Nelson, David Lee; Dos Santos, Wallans T.P.; Clososki, Giuliano C.; Lopes, Norberto P.; Klein, Stanlei I. [UNESP]; Zanatta, Lucas D. (Sociedade Brasileira de Quimica (SBQ), 2018)
The amorphous, mesoporous SiO2-SO3H catalyst with a surface area of 115 m2 g-1 and 1.32 mmol H+ per g was very efficient for the protonation of ketones on a 10% (m/m) basis, and the catalyst-bound intermediates can be trapped by polyalcohols to produce ketals in high yields or suffer aldol condensations within minutes under low-power microwave irradiation. The same catalyst can easily reverse the ketalization reaction. Printed in Brazil-
Keywords: Ketal hydrolysis; Ketalization; Protonated ketones; Self-aldolization; Sulfonated silica